RANCANG BANGUN SISTEM MONITORING NILAI pH DAN KADAR KEKERUHAN AIR PADA KOLAM TERNAK KODOK LEMBU BERBASIS IoT - Ketut Dharma Yasa; I Gusti Ngurah Janardana; I Nyoman Budiastra (Program Studi Teknik Elektro UNUD, 2020)
Frog thigh meat is one of the potential non-oil and gas export commodities. In 2011-2012 thevalue of frog thigh meat exports decreased from 4.152 tons to 2.694 tons. The scarcity of toadsavailable is due to massive hunting and the spread of red leg syndrome. Red leg syndrome is causeddue to lack of monitoring of the condition of the bull frog pond. A harassment solution is needed byutilizing the Internet-based technology of Things as an effort to create an environment, especially theright water content of the bull frog, so as to reduce the number of bull frogs affected by the disease.This tool is able to monitor pH values and water turbidity levels in aquaculture ponds through theThingspeaks platform. The test was carried out in one of the Beetle Fodder Animal HusbandryGroups located in Buduk Village, Mengwi District, Badung Regency. It was found that the pH value inthe pond was 6.5-8 and the turbidity level was 3,8-9 NTU. Based on these results, aquaculture pondsare in accordance with water standards for the life of a bull toad with a pH value of 6.5-8.5 andturbidity levels of 1.2-11.6 NTU